Exploring creative software requirements from crowd using morphological matrix - Tuan Mohd. Amin, Tengku Azharudin; Hassan, Sa’adah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The increasing trend of technology has changed the users’ expectation towards software product. In which, the successful of software product is mainly reliant on their creative and innovative features. Thus, creative ideation becomes a focal issue in software development, particularly in requirements engineering process for generating creative and innovative software requirements. Subsequently, software developers realize the benefits of crowd where it involves a wide diversity of stakeholders to express their perceptions or ideas about the software product. The various ideas from the crowd are useful as a source of software requirements, specifically for creative requirements. However, to filter and analyze the large amount and heterogeneous ideas from the crowd is a great challenge. Considering the benefits of morphological approach, thus, in this paper we demonstrate the application of morphological matrix to discover creative requirements from the crowd in a case study.